Social Media, Digital Activism, and Online Gender-Based Violence in Indonesia - Eny Ratnasari; Suwandi Sumartias; Rosnandar Romli (Nyimak: Journal of Communication, 2021)
Online Gender-Based Violence (OGBV) cases in Indonesia are increasing every year. The Indonesian people have not considered the issue of OGBV as an important thing. This study aims to explore digital activism carried out by SAFEnet (Southeast Asia Freedom of Expression Network) in the “Awas KBGO!” (Beware of OGBV!) Campaign. This research is qualitative research with a case study approach. Researchers want to know the role of social media in digital activism internally (inward) and externally (outward). Data collection techniques are interviews, observation, and literature study. The research subjects were campaign makers, campaign partners, and the target audience of the campaign. The results showed that social media has an important role in digital activism in the “Awas KBGO!” (Beware of OGBV!) Campaign. After conducting the analysis, the researchers found three major themes in the digital activism research conducted by SAFEnet, such as (1) Information Sources; (2) Movement, Mobilization, and Self-Mediation; (3) Online Gender-Based Violence Victims Advocacy.Keywords: Digital activism, online movement, online gender-based violence (OGBV), social media ABSTRAKKasus Kekerasan Berbasis Gender Online (KBGO) di Indonesia naik setiap tahun. Masyarakat Indonesia pun belum menganggap isu KBGO merupakan suatu hal yang penting. Penelitian ini bertujuan untuk mengeksplorasi aktivisme digital yang dilakukan oleh SAFEnet (Southeast Asia Freedom of Expression Network) dalam kampanye “Awas KBGO!”. Penelitian ini adalah penelitian kualitatif dengan pendekatan studi kasus. Peneliti ingin mengetahui peran media sosial dalam aktivisme digital secara internal (inward) dan eksternal (outward). Teknik pengumpulan data yaitu wawancara, observasi, dan studi pustaka. Subjek penelitian adalah pembuat kampanye, mitra kampanye, dan target audiens kampanye. Hasil penelitian menunjukkan bahwa media sosial memiliki peran penting dalam aktivisme digital dalam kampanye “Awas KBGO!”. Setelah dilakukan analisis, peneliti menemukan tiga tema besar dalam penelitian aktivisme digital yang dilakukan SAFEnet dalam kampanye “Awas KBGO!” yaitu: (1) Sumber Informasi; (2) Pergerakkan, Mobilisasi, dan Self-Mediation; (3) Advokasi Korban Kekerasan Berbasis Gender Online.   Kata Kunci: Aktivisme digital, gerakan siber, kekerasan berbasis gender online, media sosial